Performance in the Entrance Examination and its Impact on Academics and Executive Placements with Reference to Business Schools - Palkar, Apoorva; Marathe, M. (Indian Journal of Marketing, 2004)
A large number of business schools and institutes offer business management education of various competences across the country. Business schools today are facing new challenges, as industry places greater demands on the skills and competence of business school graduates. On one hand, efficient training programmes rely on a careful analysis of the competence expected from students at the end of their studies. The identification of the knowledge and know-how required to succeed will constitute the guiding principle in the design of the training process. Although this might be relatively easy in a stable environment, where competence is not destined to become obsolete, it is more problematic in a changing environment.